Why you should Mini-Med School: Mini-Med School as an intervention to increase health literacy - Sergiy Shatenko (Canadian Medical Education Journal, 2020)
Background: Health literacy is an increasingly important topic in healthcare given that low health literacy is widely prevalent and linked to poorer health outcomes and higher healthcare costs. We sought to determine if a Mini-Med School delivered by medical students could prove to be an effective intervention to improve health literacy in the elderly.